An integrated approach to understanding the linkages between ecosystem services and human well‐being. Issue 5 (22nd July 2015) - Yang, Wu; Dietz, Thomas; Kramer, Daniel Boyd; Ouyang, Zhiyun; Liu, Jianguo
Abstract : In order to use science to manage human–nature interactions, we need much more nuanced, and when possible, quantitative, analyses of the interplay among ecosystem services (ES), human well‐being (HWB), and drivers of both ecosystem structure and function, as well as HWB. Despite a growing interest and extensive efforts in ES research in the past decade, systematic and quantitative work on the linkages between ES and HWB is rare in existing literature, largely due to the lack of use of quantitative indicators and integrated models. Here, we integrated indicators of human dependence on ES, of HWB, and of direct and indirect drivers of both using data from household surveys carried out at Wolong Nature Reserve, China. We examined how human dependence on ES and HWB might be affected by direct drivers, such as a natural disaster, and how human dependence on ES and direct and indirect drivers might affect HWB. Our results show that the direct driver (i.e., Wenchuan Earthquake) significantly affected both households' dependence on ES and their well‐being. Such impacts differed across various dimensions of ES and well‐being as indicated by subindices. Those disadvantaged households with lower access to multiple forms of capital, more property damages, or larger revenue reductions also experienced greater losses in HWB. Diversifying human dependence on ES helps to mitigate disaster impacts on HWB. Our findings offer strong empirical evidence that the construction of quantitative indicators for ES and HWB, especially integrated models using them, is a viable approach for advancing the understanding of linkages between ES and HWB.